Acknowledging the Burdens of ‘Blackness’ - Sederstrom, Nneka O. (HEC Forum, 2021)
The novel coronavirus of 2019 exposed, in an undeniable way, the severity of racial inequities in America’s healthcare system. As the urgency of the pandemic grew, administrators, clinicians, and ethicists became concerned with upholding the ethical principle of “most lives saved” by re-visiting crisis standards of care and triage protocols. Yet a colorblind, race-neutral approach to “most lives saved” is inherently inequitable because it reflects the normality and invisibility of ‘whiteness’ while simultaneously disregarding the burdens of ‘Blackness’. As written, the crisis standards of care (CSC) adopted by States are racist policies because they contribute to a history that treats Black Americans are inherently less than. This paper will unpack the idealized fairness and equity pursued by CSC, while also considering the use of modified Sequential Organ Failure Assessment (mSOFA) as a measure of objective equality in the context of a healthcare system that is built on systemic racism and the potential dangers this can have on Black Americans with COVID-19.